Socio-Cultural Values of Nyadran Traditional Ceremony in Tawun, Ngawi, East Java, Indonesia - Parji, Parji (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: The progress of science, technology, and information carries serious implications for the existence of regional culture in Indonesia. The process of globalization has also promoted culture in the world becomes one-dimensional and monolithic, which in turn will reduce the national identity and also negates the local culture. In this context, âNyadranâ is one form of traditional ceremonies and local culture to be preserved, because it contains the values of social, cultural, and local knowledge; and serves as a social capital that can unite people from the process of social disintegration. This research aims to inventory the important aspects of one of the regional culture, the traditional ceremony of âNyadranâ. In addition, this study also aims to analyze the values of socio-cultural of traditional ceremonies of âNyadranâ. This study used qualitative methods, with data collection techniques are observation, documentation, and in-depth interviews. The analysis technique used is descriptive qualitative with ethnographic approach. The results showed that the traditional ceremony of âNyadranâ is a heritage of the indigenous Javanese culture, which is influenced by Hindu culture and Islamic religion. The traditional ceremony of âNyadranâ has had the values of socio-cultural, inter alia: religious values, values of mutual assistance, tolerance, unity value, the value of struggle, the value of respect for the environment, and the value of cooperation. Because of that, traditional ceremony of âNyadranâ should be preserved and developed.KEY WORD: Globalization; Socio and Cultural Values; Ceremony of Nyadran; Local Wisdom; Social Integration.Â RESUME: âNilai-nilai Sosial-Budaya dalam Upacara Tradisional Nyadran di Tawun, Ngawi, Jawa Timur, Indonesiaâ. Kemajuan sains, teknologi, dan informasi membawa dampak yang sangat serius bagi eksistensi kebudayaan daerah di Indonesia. Proses globalisasi juga telah mendorong kebudayaan di dunia menjadi berdimensi tunggal dan monolitik, yang pada gilirannya akan mereduksi identitas nasional dan menegasikan pula keragaman budaya lokal. Dalam konteks ini, Nyadran merupakan salah satu bentuk upacara adat dan budaya lokal yang perlu dilestarikan, karena mengandung nilai-nilai sosial, kultural, dan kearifan lokal; serta berfungsi sebagai modal sosial yang dapat mempersatukan masyarakat dari proses disintegrasi sosial. Penelitian ini bertujuan menginventarisir aspek-aspek penting dari salah satu kebudayaan daerah, yakni upacara adat Nyadran. Disamping itu, penelitian ini juga bertujuan untuk menganalisis nilai-nilai sosio-kultural dari upacara adat Nyadran. Penelitian ini menggunakan metode kualitatif, dengan teknik pengumpulan data yang digunakan adalah observasi, dokumentasi, dan wawancara mendalam. Teknik analisis yang digunakan ialah deskriptif-kualitatif, dengan pendekatan etnografik. Hasil penelitian menunjukan bahwa upacara adat Nyadran merupakan warisan nenek moyang yang merupakan budaya Jawa asli, yang dipengaruhi oleh budaya Hindu dan agama Islam. Upacara adat Nyadran mempunyai nilai-nilai sosio-kultural, antara lain: nilai religius, nilai gotong-royong, nilai toleransi, nilai persatuan-kesatuan, nilai perjuangan, nilai penghargaan terhadap lingkungan, dan nilai kerjasama. Karena itu, upacara adat Nyadran harus dilestarikan dan dikembangkan.KATA KUNCI: Globalisasi; Nilai Sosio dan Kultural; Upacara Adat Nyadran; Kearifan Lokal; Integrasi Sosial.Â About the Author: Dr. Parji is a Senior Lecturer at the IKIP PGRI (Institute of Education and Teacher Training, Teacher Unions of the Republic of Indonesia) Madiun, Jalan Setiabudi No.85 Madiun, East Java, Indonesia. For academic interests, the author is able to be contacted via e-mail at: parjiikippgri@rocketmail.comHow to cite this article? Parji. (2016). âSocio-Cultural Values of Nyadran Traditional Ceremony in Tawun, Ngawi, East Java, Indonesiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.9(2) November, pp.287-296. Bandung, Indonesia: Minda Masagi Press and UPI Bandung, ISSN 1979-0112. Chronicle of the article: Accepted (January 15, 2016); Revised (June 15, 2016); and Published (November 20, 2016).